Sky sailors : true stories of the balloon era - Bristow, David (David L.) (Farrar Straus Giroux, 2010)
For more than a century before airplanes, people explored the sky in balloons. From 1783 to the early 1900s, aeronauts flew into storms, crossed large bodies of water, sailed over enemy armies, and soared to deadly altitudes. Illustrated in full color with dramatuc period artwork, here are the stories of the pioneers of human flight, such as daredevil Sophie Blanchard from Napoleon's France, and Solmon Andree, who lead an aerial assault on the North Pole in 1897. --from publisher description